Private Higher Education in Kazakhstan: Thirty Years of Growth and Regulation - Shaldarbekova, Amina (International Higher Education, 2025)
<h3 id="private-institutions-are-a-major-provider-of-higher-education-in-kazakhstan-the-country-has-the-most-privatized-higher-education-system-among-all-the-post-soviet-countries-this-article-discusses-how-both-the-state-and-the-market-have-contributed-to-the-private-sectors-growth" data-pm-slice="1 1 []">Private institutions are a major provider of higher education in Kazakhstan. The country has the most privatized higher education system among all the post-Soviet countries. This article discusses how both the state and the market have contributed to the private sector’s growth.